2005
DOI: 10.1295/polymj.37.186
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose/TiO2 Hybrid Spherical Microbeads Prepared by a Viscose Phase Separation Method: Control of the Distribution of TiO2 Particles in a Sphering System

Abstract: ABSTRACT:Cellulose/TiO 2 hybrid spherical microbeads were prepared by a one-step phase separation method using a cellulose xanthate aqueous solution and a sodium polyacrylate aqueous solution. Various types of cellulose/ TiO 2 hybrid spherical microbeads were obtained by using the several kinds of TiO 2 particles. The resulting hybrid spherical microbeads showed respective differences in the distribution of TiO 2 particles. EPMA observation of the surface of hybrid spherical microbead clearly showed where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…We previously reported that the distribution of inorganic particles in composite spherical microbeads prepared by viscose phase separation method depends on the zeta potential of the particles surface. 21,22 The cellulose xanthate spherical droplet is produced by the electrostatic repulsion between the xanthate CSS À and SPA COO À groups. If the zeta potential of the inorganic particles in alkaline aqueous solution (viscose is a strong base) becomes negative and their charge distribution is narrow, the electrophoretic mobility of the inorganic particles becomes larger.…”
Section: Preparation Of Cellulose/h-bn Core-shell Microbeadsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that the distribution of inorganic particles in composite spherical microbeads prepared by viscose phase separation method depends on the zeta potential of the particles surface. 21,22 The cellulose xanthate spherical droplet is produced by the electrostatic repulsion between the xanthate CSS À and SPA COO À groups. If the zeta potential of the inorganic particles in alkaline aqueous solution (viscose is a strong base) becomes negative and their charge distribution is narrow, the electrophoretic mobility of the inorganic particles becomes larger.…”
Section: Preparation Of Cellulose/h-bn Core-shell Microbeadsmentioning
confidence: 99%
“…We (1) used core-shell spherical microbeads as a thermally conductive ller; (2) developed these cellulose/h-BN core-shell spherical microbeads using phase separation of a cellulose xanthate aqueous solution (viscose). Cellulose is reportedly hybridized with inorganic materials such as TiO 2 , 21,22 diamond, SiC, Al 2 O 3 , CeO 2 (ref. 23) and various pigments; 24 (3) hybridized the cellulose/h-BN core-shell microbeads with epoxy resin, using compression molding.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides are reported to manipulate the formation of hybrid silica nanocomposites by sol-gel processes [7][8][9][10]. In the literature, different polysaccharides/mineral oxides are described such as cellulose/silica [11], alginate/silica [12] chitosan/silica [13][14][15][16], and cellulose/titania [17,18]. Conducting sol-gel chemistry in presence of biopolymer template furnishes hybrids which on calcination >450 • C results into porous materials.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that, from a technological point of view, the problem concerning the removal of reacted TiO 2 when it is applied in the form of suspensions has not been solved yet. In order to overcome this problem, a number of authors have incorporated TiO 2 in different polymer matrices in the form of spheres, layers, or films 7–11. Moreover, it has been found that composite films of PHB‐TiO 2 are effective in the sterilization and discoloration of methylene blue and rose bengal, and they are also biodegradable and environmentally friendly 12.…”
Section: Introductionmentioning
confidence: 99%